KONTRIBUSI EKONOMI DAN PERAN GANDA PEREMPUAN SERTA PENGARUHNYA TERHADAP KESEJAHTERAAN SUBJEKTIF - Puspitawati, Herien; Simanjuntak, Megawati; Hayati, Latifatul (Department of Family and Consumer Sciences, Faculty of Human Ecology, IPB University, 2012)
This research aimed to analyze the contribution of economic, double burden, and well-being of women factory labor family. This research involved 60 families that were selected purposively. Families that involved in this research were complete families whose the wife worked as factory labor. Data was collected through interview by using questionnaire. Economic contribution was measured by proportion of wife income toward family income. Double burden was measured by total number of roles and frequency of each role. Subjective well-being was measured by wife satisfaction of their life. Data was analyzed by descriptive statistic, Pearson correlation, and multiple regression. The results showed that average women’s economic contribution were 51,0 percent and double burden were categorized as moderate. Subjective well-being generally grouped as moderate. Wife’s education and balancing work and family strategy were positively correlated with subjective well-being. Subjective well-being was influenced by wife’s education and balancing work-family strategy.